Characterization of membrane-associated non-genomic progesterone receptors in cattle bull spermatozoa - VIKAS SACHAN; SOUMEN CHOUDHURY; DILIP K SWAIN; ANUJ KUMAR; ATUL SAXENA; PRATISHTHA SHARMA; AVANEESH KUMAR SINGH (Indian Journal of Animal Sciences)
The present study aimed to examine the molecular existence of the non-genomic progesterone receptors (P4) and their location in Hariana bull spermatozoa. The investigation involved the collection and processing of 64 semen ejaculates from four Hariana bulls. Following spermatozoa protein isolation, immunoblotting revealed the presence of 56 kDa protein corresponding to progesterone (P4) membrane receptors, and the results were validated using RT-PCR, which indicated an amplicon of 466 bp. Immuno-fluorescence technique was used to confirm the location of P4-membrane receptors in spermatozoa. The present study revealed the presence of 56 kDa protein representing progesterone receptors at the acrosome as well as post-acrosomal region of Hariana cattle bull spermatozoa.